Old southern open clusters - Hawarden, Timothy George (Department of Astronomy, 2015)
The six chapters of this thesis contain the results of four years spent in the investigation of old open clusters at the SAAO. Each chapter is a preprint of a paper which has been submitted or accepted for publication and is therefore an independent entity with its own list of acknowledgements and references. Since each chapter is intelligible without continual reference to its fellow chapters, considerable overlap has sometimes occurred. As a thesis, the end product is of necessity a little disjointed. This approach has been adopted because 'the publication of the results has higher priority than the presentation of a thesis. The style is as compact as seems consistent with reasonable clarity and I hope that reading it will not present too great a problem of digestion to those interested in the evolution of solar-type stars.